Влияние культуры Мюнхена конца XIX-начала ХХ веков на становление крымского художника М. Казаса (1889-1918) - Фращенко, Д.В. (Культура народов Причерноморья, 2014)
Статья посвящена исследованию становления художника Михаила Казаса (1889-1918) в
период его обучения в Мюнхене (1907-1911), который на рубеже XIX-ХХ веков становится одним из
культурных центров Европы. В связи с этим анализируется влияние возникшего в Германии
Югендштиля, знакомства художника с французским, русским, восточным искусством посредством
выставочной и издательской деятельности города. Рассматривается формирование творческой
манеры художника под влиянием своего учителя Анжело Янка в Мюнхенской академии художеств. Стаття присвячена дослідженню становлення художника Михайла Казаса (1889-1918) в
період його навчання в Мюнхені (1907-1911), який на рубежі XIX-ХХ століть стає одним з культурних
центрів Європи. У зв'язку з цим аналізується вплив виниклого в Німеччині Югендштиля, знайомства
художника з французьким, російським, східним мистецтвом за допомогою виставкової та видавничої
діяльності міста. Розглядається формування творчої манери художника під впливом свого вчителя
Анжело Янка у Мюнхенській академії мистецтв. The article investigates the formation of the artist Michael Kazas (1889-1918) during his studying in
Munich (1907-1911), the cultural center of Europe of the late XIX – yearly XX centuries. In this connection,
influence of arisen in Germany Jugendstil, exhibition and publishing activities of the French, Russian, oriental
art is analyzed. Fraschenko D.V. considers the features of the personal artist’s perception of the social and
cultural environment of Munich. M. Kazas’s teacher Angelo Jank at the Munich Academy of Fine Arts also
influenced the formation of the creative manner of the artist.
The author comes to the conclusion that the professional school of Munich has determined the career of an artist
within the Modern Style. The artist took its flatness, decorative variant that was uncharacteristic of German art.
Munich, as one of the centers, that were attractive for the Russian artists, introduced to Kazas the activity of the
«Mir iskusstva», which was intimate to him, and led him to further creative searches.